Public Relations di Era Digital: Menghadapi Tantangan dan Peluang Baru - Sofiah, Alfiani Farhatus (Maliki Interdisciplinary Journal, 2025)
In an effort to improve public relations both inside and outside the company, public relations plays a role as a liaison between the community and company leadership. Meanwhile, all aspects of life have developed in the digital era and are completely digital. In the era of industrial digitalization, public relations has emerged as the most important symbol. It functions as a communication tool or message channel that provides possibilities and problems over time. The aim of this research is to find out how PR can overcome the benefits and problems of the digital era. Approaching the research methodology of this research is a literature review or literature study. The research findings show that PR practitioners can make appropriate plans to face new obstacles and possibilities in the digital era by applying this SWOT analysis technique